2008
DOI: 10.1016/j.pep.2008.03.002
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of detergent purified recombinant rat liver monoamine oxidase B expressed in Pichia pastoris

Abstract: The high level expression and purification of rat monoamine oxidase B (rMAOB) in the methylotrophic yeast Pichia pastoris is reported. Nearly 100 mg of purified rMAOB is obtained from 130 grams (wet weight) of cells (0.5 liter of culture). The MALDI-TOF mass spectrum of the purified protein shows a single species with a molecular mass of 59.228 ± 0.064 kDa, which agrees with the calculated molecular weight of 59.172 kDa for the rMAOB protein sequence assuming one mole of covalent FAD per mole of the enzyme. Co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
3
3
1

Relationship

3
4

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 27 publications
1
8
0
Order By: Relevance
“…In agreement with published data on hMAO A (Miller and Edmondson, 1999), on bovine MAO B (Walker and Edmondson, 1994), and on human and rat MAO B (Newton-Vinson, et al,2000;Li, 2006; Upadyhay and Edmondson, 2008), zMAO exhibits deuterium kinetic isotope effects on benzylamine analogue oxidation with D k cat and D ( k cat /K m ) values ranging from 2 to 8 (Table 4). These data demonstrate the α-C-H bond cleavage step contributes to the rate limitation in catalysis as is found with MAO A and B from various mammalian sources (Edmondson, 2009).…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…In agreement with published data on hMAO A (Miller and Edmondson, 1999), on bovine MAO B (Walker and Edmondson, 1994), and on human and rat MAO B (Newton-Vinson, et al,2000;Li, 2006; Upadyhay and Edmondson, 2008), zMAO exhibits deuterium kinetic isotope effects on benzylamine analogue oxidation with D k cat and D ( k cat /K m ) values ranging from 2 to 8 (Table 4). These data demonstrate the α-C-H bond cleavage step contributes to the rate limitation in catalysis as is found with MAO A and B from various mammalian sources (Edmondson, 2009).…”
Section: Resultssupporting
confidence: 90%
“…Previous work from this laboratory has shown the successful expression, purification, and partial characterization of recombinant zMAO (Arslan and Edmondson, 2009). This laboratory has also expressed, purified, and characterized human and rat MAO A and MAO B (Newton-Vinson, et al 2000; Li, et al 2002; Upadhyay and Edmondson 2008; Wang and Edmondson, 2009). Therefore, the tools are in place for a detailed comparative functional study of zMAO with those of human MAO A and MAO B.…”
Section: Introductionmentioning
confidence: 99%
“…Recombinant rat liver MAO A and MAO B were expressed and purified in Pichia pastoris strain KM71 as described previously (17, 18). The purified enzymes were stored in 50 mM potassium phosphate containing 50% (w/v) glycerol and 0.8% (w/v) β–octylglucopyranoside (pH 7.2) at −20°C.…”
Section: Methodsmentioning
confidence: 99%
“…Preliminary trials showed zMAO activity does not bind to DEAE Sepharose or to BioRad High-Q resin in contrast to what is observed with human or rat MAO A and MAO B [5-7]. Therefore, an alternate column purification procedure was adopted.…”
Section: Methodsmentioning
confidence: 99%
“…To aid in this effort, this laboratory has developed high level expression systems and purification protocols for the expression and purification of human and rat MAO A and of MAO B [5-7]. The rational for this work is to provide a bridge of knowledge between animal models (the rat) with the human in MAO inhibitor development.…”
Section: Introductionmentioning
confidence: 99%